Study of acquisition streetlights background signal by multi-sensor array - Yue, Wu; Changhong, Shi; Wei, Yang (2010 International Conference on Control, Automation and Systems, 2010)
The multi-sensor array, such as the sound, light, infrared, vibration etc, is used to get the street lights environmental information. Combined with a variety of clock control strategy for control lamps, it can achieve the background information of perception, detection, identification, and collect the typical characteristics of an effective signal, to rationally determine the threshold value range in the circuit design and lay a solid foundation for the realization of intelligent control of lights. The joint acquisition streetlights background signal through a variety of sensors carried out in a typical experimental design and preparation, principles, introduction, experimental methods and experimental analysis of the results, not only can test the design of control circuit, but also optimize the choice of the sensor models to provide true comparative data. In order to facilitate in a real environment to detect and further identify goals, to achieve the typical information data fusion of specific objectives, the ultimate street intelligent control can be achieved. Experimental results show that the magnetic sensors and infrared sensors detect close proximity, so the model of sensor needs to be replaced or further improved design (such as the optimization of pre-level filtering and amplification circuit design). Acoustic sensors and vibration sensors to detect distance, can meet night lighting control at residents of the community as well as tourist attractions. But there are a lot of distances to meet the use demands of roads and high-speed traffic, the more optimal designs and experiments is need. In addition, a range problem of information synchronize data collection, background noise and a variety of information data crosstalk need to be solved in the joint acquisition experiments, which in the paper were discussed.